2005
DOI: 10.1007/s11175-005-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of the Nafion—polyaniline—palladium composite electrodes

Abstract: Effect of conditions of deposition of palladium onto a composite polymeric film Nafion-polyaniline on the properties of the system thus obtained is studied. It is shown that the effect of the said conditions on the character of distribution of palladium in a polymer may be used when estimating electrocatalytic potentialities of such composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, extensive work has been focused on Nafion ® membranes modified with conducting polymers, such as polyaniline [22], polyaniline/silica [23] paying special attention to the methanol crossover in the composite membranes. It is worth noting that the mix of electronic conductivity of polyaniline with the ionic conductivity of cation-exchange membranes has also promoted the study of these composites for electrode modifications [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive work has been focused on Nafion ® membranes modified with conducting polymers, such as polyaniline [22], polyaniline/silica [23] paying special attention to the methanol crossover in the composite membranes. It is worth noting that the mix of electronic conductivity of polyaniline with the ionic conductivity of cation-exchange membranes has also promoted the study of these composites for electrode modifications [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, very few teams have studied the Nafion−PANI composite membranes. Nafion−PANI composites have been studied mostly for electrode modifications in order to mix the electronic conductivity of PANI and the ionic conductivity of Nafion.
1 Structure of Nafion
…”
Section: Introductionmentioning
confidence: 99%
“…Nafion-PANI composites have been studied mostly for electrode modifications in order to mix the electronic conductivity of PANI and the ionic conductivity of Nafion. [19][20][21][22][23] Prior to this work, we have demonstrated the possibility of improving the permselectivity of poly(styrene sulfonic acid) membranes for the transport of protons against bivalent cations (Zn 2+ and Cu 2+ ) by modifying these membranes with a thin layer of polyaniline. 24,25 It was also shown that the permselectivity behavior was linked to the location of the PANI layer within the membrane matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery to metallic palladium occurs in the region of potentials from 0.6 to 0.25 V, and oxidation to Pd 2+ at the reverse of the potential to the anode side -from 0.6 to 0.9 V. Such a large potential difference, from 0.2 to 0.6 V, indicates that the recovered Pd 0 is on the working electrode in the form of adsorbed clusters. It should be noted that in this potential range, from 0.3 to 0.6 V, the PAN is in an electrically conductive state (in the form of emeraldine), which indicates that the polymer matrix provides conditions for charge transport [17,18].…”
Section: Features Of Obtaining a Polyaniline Electrode With Embedded ...mentioning
confidence: 93%